Impact of organizational trust on job performance: a study of land and survey department / Kuldip Singh - Singh, Kuldip (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2018)
This study examines the influence of organizational trust on job performance by analyzing perceptions of 100 public employees in the Land and Survey Department. The instrument used to measure organizational trust was adopted from Institute for Public Relations (2003). Job performance was measured using an instrument developed by Borman and Motowidlo (1997). Results of the instrument’s Cronbach Alpha measurement show that the score of reliability is above .90 which indicates an acceptable level. The results indicate that organizational trust is positively correlated with job performance. These results imply that job performance may be dependent on organizational trust in the public sector. This study provides insights on the relationship between organizational trust and job performance in the public sector. The findings of this study may help public sector to enhance its organizational trust and its effect on job performance. Limitations and recommendations are also discussed.